2019
DOI: 10.1038/s41418-019-0345-2
|View full text |Cite
|
Sign up to set email alerts
|

Sam50–Mic19–Mic60 axis determines mitochondrial cristae architecture by mediating mitochondrial outer and inner membrane contact

Abstract: Mitochondrial cristae are critical for efficient oxidative phosphorylation, however, how cristae architecture is precisely organized remains largely unknown. Here, we discovered that Mic19, a core component of MICOS (mitochondrial contact site and cristae organizing system) complex, can be cleaved at N-terminal by mitochondrial protease OMA1 under certain physiological stresses. Mic19 directly interacts with mitochondrial outer-membrane protein Sam50 (the key subunit of SAM complex) and inner-membrane protein … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 55 publications
4
77
0
Order By: Relevance
“…In mammalian cells, MICOS and SAM form a stable supercomplex that was termed mitochondrial intermembrane space bridging complex (MIB) (Fig. ) . These interactions support the import of a subset of mitochondrial proteins, and, importantly, they establish contact sites between the two mitochondrial membranes .…”
Section: The Mitochondrial Contact Site and Cristae Organizing Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…In mammalian cells, MICOS and SAM form a stable supercomplex that was termed mitochondrial intermembrane space bridging complex (MIB) (Fig. ) . These interactions support the import of a subset of mitochondrial proteins, and, importantly, they establish contact sites between the two mitochondrial membranes .…”
Section: The Mitochondrial Contact Site and Cristae Organizing Systemmentioning
confidence: 99%
“…By bridging the membranes, contact sites also play a role in phospholipid transfer and biosynthesis (see section on ‘Non‐bilayer‐forming phospholipids’). Moreover, multiple studies have found that downregulation of SAM decreases the number of crista junctions , suggesting that contact sites are required for crista junction stability, perhaps by acting as an anchor. Contact site formation does not depend on the entire MICOS complex, but is mediated by the MIC60 subcomplex.…”
Section: The Mitochondrial Contact Site and Cristae Organizing Systemmentioning
confidence: 99%
See 3 more Smart Citations